Religiosity, Crime, and Drug Use Among Juvenile Offenders: A Latent Growth Modeling Approach - Jang, Sung Joon (Journal of quantitative criminology, 2019)
This study tests whether a juvenile offender's religious involvement or religiosity is inversely related to crime (i.e., non-drug offending) and use of licit and illicit drug when their trajectories are examined. It also tests whether the relationships are attributable in part to psychosocial correlates of religiosity as well as crime and drug use.